Erosion of Northern Reservoir Shores: An Analysis and Application of Pertinent Literature - Lawson,D E (1985)
This monograph describes the current state of knowledge of northern reservoir shore erosion, primarily by examining the results of erosional studies on lakes, coasts and rivers. The major erosional processes of reservoir beaches and bluffs and their mechanics are discussed in detail. Thermal and physical parameters affecting the erodibilty of shores, the environmental impacts of erosion, and the basic characteristics of the unique reservoir environment are reviewed. Current models of shore zone development are also presented. This literature analysis revealed that knowledge of erosion and recession in northern impoundments is severely limited. Quantitative analyses of the processes of erosion and their relative importance, parameters determining the nature, rate and timing of erosion, and models to predict the erodibility of a shore for use in minimizing shoreline recession remain in need of basic field research. Originator supplied keywords: Cold regions, Erosion models, Freeze-thaw, Ground water, Ice cover, Lakes, Overland flow, Permafrost, Rates, Recession, Reservoirs, Shores, Slope movement, Water level, Waves.